Analisis Keterampilan Latihan Egrang Siswa Putra Dan Putri Berdasarkan Kemampuan Keseimbangan Koordinasi Mata Tangan Dan Koordinasi Mata Kaki Di Man 1 Lebong: Analysis of Stilt Training Skills for Male and Female Students Based on the Ability to Balance Eye-Hand Coordination and Eye-Foot Coordination in Man 1 Lebong - Andin Saputra; Tono Sugihartono; Ari Sutisyana (Universitas Bengkulu, 2023)
Abstract This study aims to determine the level ofstilt training skills of male and female students based on the ability to balance hand-eye coordination and eye-foot coordination in man 1 lebong. This study uses quantitative descriptive research with survey methods, data collection techniques with tests and measurements, stork stand test instruments, throw and catch balls, mitchel soccer tests, and stilt playing tests. The subjects in this study were 30 students. the results of data analysis, description, testing of research results, and discussion, it can be concluded that the level ofStilt training skills of male and female students based on the ability to balance hand eye coordination and eye-foot coordination in Man 1 Lebongis in the